Computed tomography-guided microwave ablation for right middle lobe pulmonary nodules: a retrospective, single-center, case-control study - Yanting Hu; Guoliang Xue; Xinyu Liang; Zhichao Li; Nan Wang; Pikun Cao; Gang Wang; Haitao Zhang; Xiaohuan Zheng; Aiguang Wang; Wenhua Zhao; Cuiping Han; et al. (International Journal of Hyperthermia)
Purpose This retrospective, single-center, case-control study evaluated the safety and efficacy of Computed tomography (CT)-guided microwave ablation (MWA) for pulmonary nodules located in the right middle lobe (RML), a challenging location associated with a high frequency of complications.Methods Between May 2020 and April 2022, 71 patients with 71 RML pulmonary nodules underwent 71 MWA sessions. To comparison, 142 patients with 142 pulmonary nodules in non-RML were selected using propensity score matching. The technical success, technique efficacy, complications, and associated factors were analyzed. The duration of the procedure and post-ablation hospital stay were also recorded.Results Technical success was achieved in 100% of all patients. There were no significant differences in technique efficacy rates between the RML and non-RML groups (97.2% vs. 95.1%, p = 0.721). However, both major (47.9% vs. 19.7%, p < 0.001) and minor (26.8% vs. 11.3%, p = 0.004) pneumothorax were more common in the RML group than non-RML group. MWA for RML pulmonary nodules was identified as an independent risk factor for pneumothorax (p < 0.001). The duration of procedures (51.7 min vs. 35.3 min, p < 0.001) and post-ablation hospital stays (4.7 days vs. 2.8 days, p < 0.001) were longer in the RML group than non-RML group.Conclusions CT-guided MWA for RML pulmonary nodules showed comparable efficacy compared with other lobes, but posed a higher risk of pneumothorax complications, necessitating longer MWA procedure times and extended hospital stays.